2019
DOI: 10.1002/uog.20265
|View full text |Cite
|
Sign up to set email alerts
|

Validation of competing‐risks model in screening for pre‐eclampsia in twin pregnancy by maternal factors

Abstract: Objective To examine the predictive performance of the competing‐risks model in screening for pre‐eclampsia (PE) by maternal demographic characteristics and medical history in twin pregnancy, in a training dataset used for development of the model and a validation dataset. Methods The data for this study were derived from two prospective non‐intervention multicenter screening studies for PE in twin pregnancies at 11 + 0 to 13 + 6 weeks' gestation. The first study of 2219 women, which was reported previously, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…In a previous study, we evaluated the predictive performance for PE of the competing‐risks model in singleton pregnancies using two validation datasets and demonstrated very good discrimination between affected and unaffected pregnancies and good agreement between predicted risk and observed incidence of PE. In contrast, a validation study of our competing‐risks model for twin pregnancies found that, in both the training and validation datasets, the observed incidence of PE was lower than the predicted one, especially for early PE. In this study, we developed a new model and demonstrated good agreement between predicted risk and observed incidence of PE < 34, < 37 and < 39 weeks' gestation.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In a previous study, we evaluated the predictive performance for PE of the competing‐risks model in singleton pregnancies using two validation datasets and demonstrated very good discrimination between affected and unaffected pregnancies and good agreement between predicted risk and observed incidence of PE. In contrast, a validation study of our competing‐risks model for twin pregnancies found that, in both the training and validation datasets, the observed incidence of PE was lower than the predicted one, especially for early PE. In this study, we developed a new model and demonstrated good agreement between predicted risk and observed incidence of PE < 34, < 37 and < 39 weeks' gestation.…”
Section: Discussionmentioning
confidence: 80%
“…In a study of 2219 twin pregnancies, we proposed that the same competing‐risks model developed in singleton pregnancies can be adapted for use in twins; in dichorionic (DC) and monochorionic (MC) twin pregnancies with the same characteristics as in singleton pregnancies, the distribution of gestational age at delivery with PE was shifted to the left by 8 and 10 weeks, respectively. In a subsequent validation study involving 2999 twin pregnancies, we found that the predictive performance for PE was consistent with that in the training set used for development of the model; however, calibration plots of the predictive performance of the competing‐risks model demonstrated that, in both the training and validation datasets, the observed incidence of PE was lower than the predicted one and such overestimation of risk was particularly marked for early PE. This suggested the need for a model in which the effect of twins relative to singletons in decreasing the gestational age at delivery with PE should increase with gestational age.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations